Efektivitas Penerapan E-Government dalam Meningkatkan Kualitas Pelayanan e-KTP di Kota Kupang - Indrika Amanda Junita Panggur; Mareytha F.X Mooy Watamutu; Meilianus Rivan Ware; Meliani Luhu; Sara Marlani Moduhina (Student Scientific Creativity Journal, 2026)
The rapid advancement of information and communication technology has driven the transformation of government systems toward the implementation of e-government, particularly in public service delivery such as electronic ID card (e-KTP) services. However, in developing regions, the effectiveness of digital-based services remains uneven due to various structural and social constraints. This study aims to analyze the effectiveness of e-government implementation in improving the quality of e-KTP services in Kupang City and to identify key supporting and inhibiting factors. The research employs a qualitative approach with a descriptive design, integrating literature review and field research. Data were collected through semi-structured interviews, limited observation, and document analysis involving 12 informants, consisting of government officials and service users, selected through purposive sampling. Data analysis was conducted using an interactive model, including data reduction, data display, and conclusion drawing, supported by source triangulation to ensure validity. The findings indicate that while e-government implementation has contributed to more structured administrative processes, its effectiveness remains partial and context-dependent. Key challenges include limited technological infrastructure, unstable system performance, low digital literacy among citizens, and insufficient human resource capacity. In practice, services are still hybrid, combining digital and face-to-face interactions. The study concludes that e-government effectiveness is shaped by the interaction between technological systems, organizational capacity, and community characteristics. Therefore, improving servicequality requires strengthening infrastructure, enhancing staff competencies, and promoting digital literacy to achieve more effective, efficient, and inclusive public services.